Abnormal expression of homeobox genes and transthyretin in C9ORF72 expansion carriers. (August 2017) - Finch, NiCole A.; Wang, Xue; Baker, Matthew C.; Heckman, Michael G.; Gendron, Tania F.; Bieniek, Kevin F.; Wuu, Joanne; DeJesus-Hernandez, Mariely; Brown, Patricia H.; Chew, Jeannie; Jansen-West, Karen R.; Daughrity, Lillian M.; et al.
Abstract : Objective: We performed a genome-wide brain expression study to reveal the underpinnings of diseases linked to a repeat expansion in chromosome 9 open reading frame 72 ( C9ORF72 ). Methods: The genome-wide expression profile was investigated in brain tissue obtained from C9ORF72 expansion carriers (n = 32), patients without this expansion (n = 30), and controls (n = 20). Using quantitative real-time PCR, findings were confirmed in our entire pathologic cohort of expansion carriers (n = 56) as well as nonexpansion carriers (n = 31) and controls (n = 20). Results: Our findings were most profound in the cerebellum, where we identified 40 differentially expressed genes, when comparing expansion carriers to patients without this expansion, including 22 genes that have a homeobox (e.g., HOX genes) and/or are located within the HOX gene cluster (top hit: homeobox A5 [ HOXA5 ]). In addition to the upregulation of multiple homeobox genes that play a vital role in neuronal development, we noticed an upregulation of transthyretin ( TTR ), an extracellular protein that is thought to be involved in neuroprotection. Pathway analysis aligned with these findings and revealed enrichment for gene ontology processes involved in (anatomic) development (e.g., organ morphogenesis). Additional analyses uncovered that HOXA5 and TTR levels are associated with C9ORF72 variant 2 levels as well as with intron-containing transcript levels, and thus, disease-related changes in those transcripts may have triggered the upregulation of HOXA5 and TTR . Conclusions: In conclusion, our identification of genes involved in developmental processes and neuroprotection sheds light on potential compensatory mechanisms influencing the occurrence, presentation, and/or progression of C9ORF72 -related diseases.